The Diverse Function of PD-1/PD-L Pathway Beyond Cancer - Qin, Weiting; Hu, Lipeng; Zhang, Xueli; Jiang, Shuheng; Li, Jun; Zhang, Zhigang; Wang, Xu (Frontiers in Immunology, 2019)
The recent success of PD-1/PD-L1 blockade in cancer therapy illustrates the importance of PD-1/PD-L1 pathway in the regulation of antitumour immune responses. However, regulating signaling by PD-1/PD-L pathway is also associated with substantial inflammatory effects that can resemble autoimmune responses, chronic infection and sepsis, which is consistent with the role of this pathway in balancing protective immunity and immunopathology, homeostasis and tolerance. Targeting PD-1/PD-L1 to treat cancer has shown benefits in many patients, suggesting a promising opportunity to stimulate this pathway in autoimmune and inflammatory disorders. Here, we review the current understanding of the PD-1/PD-L pathway on immune-mediated diseases and the relevant mechanisms that control such immune reaction.